2020
DOI: 10.1073/pnas.2016158117
|View full text |Cite
|
Sign up to set email alerts
|

Mesyl phosphoramidate backbone modified antisense oligonucleotides targeting miR-21 with enhanced in vivo therapeutic potency

Abstract: The design of modified oligonucleotides that combine in one molecule several therapeutically beneficial properties still poses a major challenge. Recently a new type of modified mesyl phosphoramidate (or µ-) oligonucleotide was described that demonstrates high affinity to RNA, exceptional nuclease resistance, efficient recruitment of RNase H, and potent inhibition of key carcinogenesis processes in vitro. Herein, using a xenograft mouse tumor model, it was demonstrated that microRNA miR-21–targeted µ-oligonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…The MsPA modifcation was recently reported by Stetsenko as an alternate for PS in uniform DNA ASOs targeting miR-21 ( 13 ). Uniform DNA MsPA oligonucleotides administered in complex with folate-containing liposomes demonstrated RNaseH1-mediated inhibition of primary tumor growth by downregulating miR-21 in tumors and increased biosynthesis of miR-21–regulated tumor suppressor proteins ( 12 ). Peritumoral administration of MsPA DNA ASOs resulted in efficient accumulation in the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MsPA modifcation was recently reported by Stetsenko as an alternate for PS in uniform DNA ASOs targeting miR-21 ( 13 ). Uniform DNA MsPA oligonucleotides administered in complex with folate-containing liposomes demonstrated RNaseH1-mediated inhibition of primary tumor growth by downregulating miR-21 in tumors and increased biosynthesis of miR-21–regulated tumor suppressor proteins ( 12 ). Peritumoral administration of MsPA DNA ASOs resulted in efficient accumulation in the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The mesylphosphoramidate (MsPA) linkage was recently reported by Stetsenko as an alternate to PS for RNaseH1-mediated knock down of micro RNA targets and to modulate mRNA splicing ( 12–14 ). In the MsPA linkage, one of the non-bridging oxygen atoms in the phosphodiester linkage is replaced with methanesulfonylamido group (Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PS and 2’-OMe RNA techniques are also broadly used as miRNA antisense inhibitors to block the functions of miRNAs [ 86 , 88 ]. Even more, new modified mesyl phosphoramidate RNA targeting to miRNAs has shown more efficient to block miRNA functions [ 89 ]. These results suggest the increase of miRNA stability to prolong half-life is a critical step to apply miRNA therapy, and synthetic biology would also play an important role for this application.…”
Section: Micrornamentioning
confidence: 99%
“…The obtained lipid-oligonucleotide conjugates (LONs) can be conveniently isolated by the usual C18 reverse-phased HPLC, due to significant difference in retention times with unmodified oligonucleotides (see Supplementary Materials) for HPLC profiles and ESI-MS spectra). Our preliminary data have shown that such lipophilic groups are fully compatible with other phosphate group modifications such as phosphorothioate, mesyl phosphoramidate [27,37,38] and phosphoryl guanidine [39].…”
Section: Discussionmentioning
confidence: 71%